Indicators of child health in pastoral communities in the Karakoram and Hindukush mountains, Pakistan - Spenta Kakalia (Journal of the Pakistan Medical Association, 2021)
Pastoralism is practiced in remote parts of the Karakoram and Hindukush high mountains, which sprawl across Northern Pakistan, with women and children travelling to high pastures with their animals during summer. There is no road access; glaciers and hazardous terrain accentuate their remoteness. This was a cross-sectional observational study, carried out along Pakistan’s border with Afghanistan’s Wakhan province. A questionnaire was used to collect basic health data. Height / length, and weight were also measured; 35 children were included in the study. This paper offers preliminary conclusions about health indicators and access to health care. For children in the pastures, health care, and other amenities entail long and sometimes hazardous journeys. Living at high altitudes with their livestock, nutrition consists almost exclusively of wheat (roti) and dairy products. Continuous...